The Effect of Different File Motions on the Formation of Apical Debris During Root Canal Preparation - Deval Kumar Arora; Alakesh Singha; Sarah Salah Gaafar; Nirav Parmar; Priyanshi Kankriya; Nivedita Sahoo; Hiren Hansraj Patadiya (Journal of Pharmacy and Bioallied Sciences)
Background: The formation of apical debris is a common occurrence during root canal preparation, which may cause postoperative complications like pain and infection. Different file motions—rotary, reciprocating, and adaptive—can influence the extent of debris extrusion. Materials and Methods: A total of 90 extracted single-rooted teeth were randomly divided into three groups (n = 30) based on the file motion used: Group 1—rotary, Group 2—reciprocating, and Group 3—adaptive motion. All teeth were standardized to a working length of 18 mm, and canals were prepared using a crown-down technique with a size #25 file at the apex. The extruded debris was collected in pre-weighed Eppendorf tubes, dried, and weighed again to determine the amount of debris. The preparation time for each file system was also recorded. Results: The mean weight of apical debris (in mg) was as follows: Rotary group: 0.62 ± 0.05 mg, Reciprocating group: 0.82 ± 0.07 mg, and Adaptive motion group: 0.48 ± 0.04 mg. The adaptive motion files produced significantly less debris than rotary and reciprocating files (P < 0.05). The reciprocating group showed the highest amount of apical debris. There was no significant difference in preparation time among the three groups. Conclusion: File motion has a significant effect on the formation of apical debris during root canal preparation. Adaptive motion files resulted in the least debris extrusion, while reciprocating files caused the highest amount of debris. These findings highlight the importance of choosing an appropriate file motion to minimize apical debris and reduce the risk of postoperative complications.